2002
DOI: 10.1148/radiol.2251011225
|View full text |Cite
|
Sign up to set email alerts
|

Multi–Detector Row Helical CT in Preoperative Assessment of Small (≤1.5 cm) Liver Metastases: Is Thinner Collimation Better?

Abstract: Image reconstruction with multi-detector row helical CT at collimations less than 5 mm may not improve sensitivity in the detection of hepatic metastases 1.5 cm or smaller.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
3
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(49 citation statements)
references
References 24 publications
2
41
3
3
Order By: Relevance
“…They then compared reconstructed images at collimation of 5, 3.75 and 2.5 mm with 50% overlap. They did not obtain an improved sensitivity in the detection of small hepatic metastases with reconstructed images at collimation less than 5 mm [26]. When we used 5 mm reconstructed slice thickness, we observed that similar results were obtained with mm per rotation.…”
Section: Discussionsupporting
confidence: 60%
“…They then compared reconstructed images at collimation of 5, 3.75 and 2.5 mm with 50% overlap. They did not obtain an improved sensitivity in the detection of small hepatic metastases with reconstructed images at collimation less than 5 mm [26]. When we used 5 mm reconstructed slice thickness, we observed that similar results were obtained with mm per rotation.…”
Section: Discussionsupporting
confidence: 60%
“…Past publications have been quite restricted here and recommended that the slice thickness should not be ! 5 mm for the low-contrast organ liver [8,9] . Recent publications, however, disocvered advantages for a reconstructed slice thickness down to 3 mm [10] .…”
Section: Computed Tomographymentioning
confidence: 99%
“…From the viewpoint of hemodynamics, few HCCs ≤5 mm in diameter exhibit hypervascularity during the course of their growth, except for intrahepatic metastases, and collimation at 5 mm is therefore considered appropriate for screening [32]. …”
Section: Improvements On Ctmentioning
confidence: 99%